A polydopamine-based photodynamic coating on the intraocular lens surface for safer posterior capsule opacification conquering. (4th March 2022) - Qie, Jiqiao; Wen, Shimin; Han, Yuemei; Liu, Sihao; Shen, Liangliang; Chen, Hao; Lin, Quankui
Abstract : A photosensitizer Ce6 incorporated polydopamine coating was introduced onto the intraocular lens surface for effective yet safer posterior capsule opacification conquering after cataract surgery. Abstract : Intraocular lens (IOL) is the indispensable implant for cataract surgery. However, posterior capsular opacification (PCO) happens in high incidence after IOL implantation. PCO is caused by adhesion, proliferation, and trans -differentiation of the residual human lens epithelial cells (HLECs). Despite the great achievements in surface coating and antiproliferative drug loading on the intraocular lens (IOL) for effective PCO prevention, the complex fabrication process and potential toxicity of the drugs still limit their clinical applications and commercial mass production. In this investigation, a convenient and efficient photodynamic therapy (PDT) coating fabricated by facile yet economical and practical dopamine self-polymerization was applied to IOL surface modification for PCO prevention. The optical properties of IOL, such as light transmittance, imaging quality and refractive index, remain unchanged after modification. Using an in vitro cell assay, the parameters of PDT were optimized. The PDT coating shows excellent biocompatibility in darkness and eliminates LECs significantly under irradiation. The research on the cell elimination mechanism showed that reactive oxygen species (ROS) mainly induced cell apoptosis. In vivo experiments demonstrated that the implantation of modified IOLs can prevent PCO effectively. As a result, this work provides a safe, simple and effective PDT coating for the IOL surface to reduce the incidence of PCO.